O imaginário do milagre e a religiosidade popular: um estudo sobre a prática votiva nas Minas do século XVIII - Jean Luiz Neves Abreu (2001)
This work endeavours to study the ex-votos into the 18th century Minas Gerais society and its relationship with the popular religiosity. Ex-votos tradition has its roots in the paganism, it was incorporated by cristianism during the Middle Age and became popular in catholic Europe especially in the Iberian countr ies during the Modern History.An ex-voto is every kind of object wich is offered to a saint in order to thank for a miracle. People use to make replicas of parts of the human body and to draw or to paint the ex-votos. The picture of the ex-votos are the principal source of this research. They were diffused in Brazil mainly in Minas Gerais by portuguese settlers during the 18th century from then on, it became a custom among all social levels. The ex-votos are used to thank for the cure of an illness and, in the Minas Gerais society of the 18th century, the represented the suffering of the body. In a way, we can saythat their objective was the cure and the salvation of the body. Even if there is a relationship between the ex-voto custom and the supernatural, it is a custom which does not belong to the ecclesiastical culture. In this way, that shows us a kind of religiosity that turns to a pragmatic view of the World.Ex-votos tradition reveals how miracles were important to the people of the 18th century. As well as to thank for the cure of an illness, people used to turn to that custom to save the life of their sons and daughters or to thank for to be alive after a disaster. When westablish a relationship between the purpose of the ex-votos and the magical rites, we perceive that there were an affinity between them.The study of the ex-votos allowed us to understand how people can change some customs attributing a new meaning to them. People that lived in Minas Gerais in the 18th century not only used to practice their religiosity but also had a kind of a sense of religiosity in their daily life.